Pengaruh kepuasan konsumen dan promosi terhadap niat pembelian ulang konsumen shopee saat pandemi: Indonesia - Rendy Irwanto, Muhammad; Tjipto Subroto, Waspodo (Jurnal Paradigma Ekonomika, 2022)
The purpose of this study, among others, is to determine the effect of consumer satisfaction and promotion on shopee consumers' repurchase intentions during the pandemic. This study uses the student population of the 2018 Economic Education Study Program, State University of Surabaya with the criteria of having used the Shopee application at least once, totaling 57 students. The sampling technique of this research is the saturated sampling technique, which means using the entire population as a sample so that 57 students are obtained. This study uses multiple regression analysis. With a questionnaire as a data collection tool and tested for validity and reliability as well as the classical assumption test as a test instrument. The data that has been collected was analyzed by SPSS. The results showed that there was a partial positive effect of consumer satisfaction on repurchase intentions. There is a partially positive effect on promotion on repurchase intention. There is a simultaneous effect of consumer satisfaction and promotion on repurchase intention.